Institutional Study of the European Union Intelligence and Situation Centre (EU INTCEN) - A. I. Pozharov; S. A. Karyukin (Vestnik MGIMO-Universiteta)
This article delves into the intricate domain of the European Union's intelligence apparatus, notably, the European Union Intelligence and Situation Centre (EU INTCEN). Employing a historiographical analysis of both domestic and international literature, the authors synthesize insights from Russian and foreign scholars concerning the genesis of intelligence operations in a unified Europe, focusing on their structural attributes. Furthermore, this study seeks to evaluate the contemporary state and potential directions of the EU's intelligence activities, considering both their functional and institutional dimensions.